Pembuatan Aplikasi News Dwi Pekan Universitas Kristen Petra Berbasis Android - Harris Boedijono; Justinus Andjarwirawan; Alexander Setiawan (Jurnal Infra, 2015)
News application is an application used to read news from one or more sources. The development of this Android news application is based on the use of smartphones and tablets which are starting to become a necessity in today's society. The application is made so that readers can access news wherever and whenever as long as internet connection is available. News source used by the application is Dwi Pekan Petra Christian University. Until now, Dwi Pekan publishes their news in the form of print media and via the website. To maximize Dwi Pekan publication, an Android application is made so that Dwi Pekan can better reach its readers.In the application there are several features that can simplify Dwi Pekan readers in getting the best reading comfort. Dwi Pekan application provides news to be able to meet the reading needs in different types and sizes of smartphones and tablets. The application was created using Ionic Framework with JavaScript Framework AngularJS, Cordova API, and Node.js.After going through the process of testing that has been done, the application can show Dwi Pekan news and present it well. Applications can also run all the features contained in it.